(untitled) (Itinera, 2025)
The following introduction opens the present issue of Itinera by gathering a selection of the papers presented at the conference Artificial Intelligence to the Test. Creativity and Humanistic Knowledge Today (Università degli Studi di Milano, May 8–9, 2025). The issue examines how contemporary art engages with artificial intelligence not as a neutral instrument but as a dialogical partner in thought and creation. Moving beyond polarized narratives that cast AI either as a threat or as an enhancement of human capacities, the introduction explores the relational space in which human and machine agencies interact, generating new meanings and aesthetic possibilities. By foregrounding interaction rather than autonomy or technical performance, it proposes a framework for understanding AI-based artistic practice as a site for rethinking authorship, intention, and the co-constitutive evolution of humans and their technologies.